PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL PADA MATA KULIAH PERSPEKTIF GLOBAL - Dyah Kumalasari (Universitas Negeri Yogyakarta, 2017)
ABSTRACT Actualization of the value of character education based on local wisdom in the course of global perspective is done in order to equip students with noble values of the nation's culture to face the swift current of globalization. Javanese ethical values such as the principle of harmony and honor principles are presented as a study material that is an important part in discussing social changes and lifestyles of society in the global era. Included in this study is the study of the typical local wisdom of the people around Yogyakarta. The student's positive response indicates that the cultural values of our ancestral heritage still allow us to lift and revive in order to fortify the young generation today from the negative effects of global culture, since this course presents many insights into global culture that leads to pop culture, . Giving awareness to students about real-world phenomena behind the meaning of words from globalization, including discussing many things about current global issues, will be more effective if done by cultivating character education based on local wisdom. Keywords: character education, culture, local wisdom, global perspective